2021
DOI: 10.3390/su13052804
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Supporting Students in Collaborative Ways—An Analysis of Collaborative Work Creating Supportive Learning Environments for Every Student in a School: Cases from Austria, Finland, Lithuania, and Poland

Abstract: Many studies have highlighted the importance of community and cooperation in inclusive education. However, traditionally, teachers are trained to manage their classes alone. Along with the aspirations of inclusive education, there is high pressure to develop school cultures that are more communal and to reorient school personnel’s work, making it more collaborative, in order to meet the diverse needs of all students. In this research, we explored and compared the collaborative ways in which teachers supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
(69 reference statements)
0
8
0
1
Order By: Relevance
“…Quality education refers to a policy that aims at improving personal quality, focuses on cultivating students' basic spirit and practical quality, and includes science, morality, art, and discipline as the basis to create students' morality, intelligence, physique, and discipline [ 14 ]. From the perspective of pedagogy, education lays more emphasis on basic functions, which refers to the sum of those stable, basic, social evaluation, and other meaningful characteristics, which can have a wide impact on the efficiency of human life and the future development of society [ 15 ].…”
Section: Theoretical Researchmentioning
confidence: 99%
“…Quality education refers to a policy that aims at improving personal quality, focuses on cultivating students' basic spirit and practical quality, and includes science, morality, art, and discipline as the basis to create students' morality, intelligence, physique, and discipline [ 14 ]. From the perspective of pedagogy, education lays more emphasis on basic functions, which refers to the sum of those stable, basic, social evaluation, and other meaningful characteristics, which can have a wide impact on the efficiency of human life and the future development of society [ 15 ].…”
Section: Theoretical Researchmentioning
confidence: 99%
“…This paper supports other findings in the academic literature on COIL. Lakkala et al's (2021) study explored and compared the collaborative ways in which students in four schools in Austria, Finland, Lithuania and Poland have been supported in their learning. The study concluded that collaborative action should be regarded as significant in creating inclusive http://dx.doi.org/10.18820/2519593X/pie.v40.i1.5 2022: 40(1) spaces to support students.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusive education is based on commonality and IPC amongst professionals, parents and learners (Lakkala et al, 2021 ). It is a reform that supports diversity amongst all learners (UNESCO, 2001 ).…”
Section: Inclusive Educationmentioning
confidence: 99%
“…Inter-professional collaboration has been recommended as a means by which the needs of learners with additional needs can be met (Gallagher et al, 2020 ). Inter-professional collaboration is a shared expertise, whereby team professionals create strategies together, learning from professionals in other fields (Lakkala et al, 2021 ). Speech–language therapists contribute specialist knowledge and skills regarding learners with DLD; they are specialists trained to diagnose and assist learners in speech–language and communication needs (SLCNs).…”
Section: The Support Of Learners With Developmental Language Disorder...mentioning
confidence: 99%
See 1 more Smart Citation